The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1002/wcc.108
|View full text |Cite
|
Sign up to set email alerts
|

Forest productivity under climate change: a checklist for evaluating model studies

Abstract: Climate change is highly likely to impact on forest productivity over the next century. The direction and magnitude of change are uncertain because many factors are changing simultaneously, such as atmospheric composition, temperature, rainfall, and land use. Simulation models have been widely used to estimate how these interacting factors might combine to alter forest productivity. Such studies have used many different types of models with different underlying assumptions. To evaluate predictions made by such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 183 publications
1
108
1
1
Order By: Relevance
“…Another source of variation in height growth might be the genetic diversity within Norway spruce [40], though provenances in Bavaria do not seem to differ greatly [41]. Furthermore phosphorus could have a strong influence on growth [42,43]. Phosphorus availability is optimal in the slightly acid to neutral pH range.…”
Section: Missing Factors Influencing Growthmentioning
confidence: 99%
“…Another source of variation in height growth might be the genetic diversity within Norway spruce [40], though provenances in Bavaria do not seem to differ greatly [41]. Furthermore phosphorus could have a strong influence on growth [42,43]. Phosphorus availability is optimal in the slightly acid to neutral pH range.…”
Section: Missing Factors Influencing Growthmentioning
confidence: 99%
“…Extreme drought events strongly affect the physiological functioning of forests, and an increase of their intensity and severity will negatively affect tree growth and vigour in sites where these are strongly limited by water availability (Breshears et al 2 index models (Ung et al, 2001). However, efforts at physiological modelling of forest decline in relation to the effects of silviculture on Mediterranean pine and the impact of global change on forest in general are scarce (Fontes et al, 2010;Medlyn et al, 2011). Process-based stand growth simulation models, based on available empirical data or known physiological processes, or both, have been developed to improve our understanding of forest behaviour on the basis of descriptions of plant-soil and carbon-nutrient-water interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, site productivity presents great spatial and temporal variability (Skovsgaard & Vanclay 2013). Climate change directly or indirectly affects forest productivity due to rising atmospheric CO2 concentration and temperatures, changes in the amount and timing of precipitation and the interactions of forest ecosystems (Kirilenko & Sedjo 2007, Medlyn et al 2011. Experiments, observations and models indicate that the forest productivity changes with climate change, but the direction and magnitude of the effects are still uncertain (Medlyn et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change directly or indirectly affects forest productivity due to rising atmospheric CO2 concentration and temperatures, changes in the amount and timing of precipitation and the interactions of forest ecosystems (Kirilenko & Sedjo 2007, Medlyn et al 2011. Experiments, observations and models indicate that the forest productivity changes with climate change, but the direction and magnitude of the effects are still uncertain (Medlyn et al 2011). Using dominant height as a measure of site productivity, Bontemps et al (2009) reported an increase of more than 50% in common beech at the end of the 20 th century in north-eastern France, whereas Badeau et al (1995) found an increase of 27%.…”
mentioning
confidence: 99%